Eksplorasi Dimensi Moralitas Remaja di Indonesia - Purwati Purwati; Muhammad Japar; Laily Qomariyah (Kuras Institute, 2022)
Moral reasoning is very important for Indonesian teenagers to have. Adolescents who understand morals will have an impact on correct behavior and avoid deviant behavior. This is supported by the ability of adolescents to think logically in determining right or wrong decisions before taking action or speaking because it is the result of considering the basic values ​​of the norms they have. The research entitled